Analysis of Students' Algebraic Reasoning Level in Learning Limit Function - Puspitasari, Ratna; Basir, Mochamad Abdul; Aminudin, Mohamad (JURNAL PENDIDIKAN MATEMATIKA, 2024)
Algebraic reasoning is essential for students to develop thinking systematically and analytically to conclude. This study analyzes students' algebraic reasoning levels about learning limit functions. The method used is a qualitative method with data collection techniques using algebraic reasoning tests on 23 first-semester students of the mathematics education study program and interviews conducted with one student from each of the high, medium, and low levels. Data analysis techniques in this study consist of data collection, reduction, presentation, and conclusions. In completing the algebraic reasoning test, students with high levels can fulfill four of the five indicators of algebraic reasoning. Students with a moderate level of algebraic reasoning can fulfill three of the five indicators of algebraic reasoning. Students with a low level of algebraic reasoning can fulfill four of the five indicators of algebraic reasoning. Students with high, medium, and low algebraic reasoning cannot find patterns, create patterns, and generalize patterns. Keywords: reasoning algebraic, function limit, generalized patterns